The cat lipocalin Fel d 7 and its cross‐reactivity with the dog lipocalin Can f 1. Issue 10 (11th July 2016) - Apostolovic, D.; Sánchez‐Vidaurre, S.; Waden, K.; Curin, M.; Grundström, J.; Gafvelin, G.; Cirkovic Velickovic, T.; Grönlund, H.; Thomas, W. R.; Valenta, R.; Hamsten, C.; van Hage, M.
Abstract: We investigated the prevalence of sensitization to the cat lipocalin Fel d 7 among 140 cat‐sensitized Swedish patients and elucidated its allergenic activity and cross‐reactivity with the dog lipocalin Can f 1. Sixty‐five of 140 patients had IgE to rFel d 7 whereof 60 also had IgE to rCan f 1. A moderate correlation between IgE levels to rFel d 7 and rCan f 1 was found. rFel d 7 activated basophils in vitro and inhibited IgE binding to rCan f 1 in 4 of 13 patients, whereas rCan f 1 inhibited IgE binding to rFel d 7 in 7 of 13 patients. Fel d 7 and Can f 1 showed high similarities in protein structure and epitopes in common were found using cross‐reactive antisera. Fel d 7 is a common allergen in a Swedish cat‐sensitized population that cross‐reacts with Can f 1, and may contribute to symptoms in cat‐ but also in dog‐allergic patients.